SiC protective coating for photovoltaic retinal prosthesis. (21st June 2016) - Lei, Xin; Kane, Sheryl; Cogan, Stuart; Lorach, Henri; Galambos, Ludwig; Huie, Philip; Mathieson, Keith; Kamins, Theodore; Harris, James; Palanker, Daniel
Abstract: Objective. To evaluate plasma-enhanced, chemically vapor deposited (PECVD) amorphous silicon carbide ( α -SiC:H) as a protective coating for retinal prostheses and other implantable devices, and to study their failure mechanisms in vivo . Approach. Retinal prostheses were implanted in rats sub-retinally for up to 1 year. Degradation of implants was characterized by optical and scanning electron microscopy. Dissolution rates of SiC, SiN x and thermal SiO2 were measured in accelerated soaking tests in saline at 87 °C. Defects in SiC films were revealed and analyzed by selectively removing the materials underneath those defects. Main results. At 87 °C SiN x dissolved at 18.3 ± 0.3 nm d −1, while SiO2 grown at high temperature (1000 °C) dissolved at 0.104 ± 0.008 nm d −1 . SiC films demonstrated the best stability, with no quantifiable change after 112 d. Defects in thin SiC films appeared primarily over complicated topography and rough surfaces. Significance. SiC coatings demonstrating no erosion in accelerated aging test for 112 d at 87 °C, equivalent to about 10 years in vivo, can offer effective protection of the implants. Photovoltaic retinal prostheses with PECVD SiC coatings exhibited effective protection from erosion during the 4 month follow-up in vivo . The optimal thickness of SiC layers is about 560 nm, as defined by anti-reflective properties and by sufficient coverage to eliminate defects.